DECISIONS OF THE ADMINISTRATIVE COUNCIL ON ROAD TRANSPORT ISSUES IN THE IMMEDIATE PERIOD AFTER THE ESTABLISHMENT OF THE KINGDOM OF POLAND IN 1815 - Marek RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The article analyses decisions taken by the main governing body - the Administrative Council (and the Tsarist Imperial Governor serving therein) in terms of drawing out the general directions and conditions of building of roads in the Kingdom of Poland during the first period of this state existence, i.e., until the emergence of the financial crisis of the public budget in the early 1820s. In particular, the decisions taken by the then government regarding the development of Polish transport were assessed in the following areas: a) main directions of road works; b) establishment of the principles of the control system; c) laws on the division and width of roads and measurements of their length, as well as on the of land occupied for the construction of tracts; d) engineering or construction personnel, use of train animals and tools, procurement of funds and construction materials, anti-corruption system and, finally, protection against destruction. The analysis of the archival data of minutes (protocols) of the Administrative Council makes it possible to conclude about the relatively very high professional level of the then legislators and policymakers, and about the existence of correctly understood vision of the transport policy of the state of the described era.